Efecto de los incendios forestales en la relación C/N del suelo. - Correa, F.G. (2021)
Forest fires affect the soil with respect to its physical, chemical and biological properties; mainly showing intense degradation, as well as the modification of the concentration values of the essential components for the fertility and productivity of the resource, especially total nitrogen (NT), organic carbon (CO) and the carbon/nitrogen ratio (C/N). The present meta-analysis aimed to analyze the effect of forest fires on the C/N ratio of the soil. In the meta-analysis, 5 areas affected by forest fires were studied: Huacraruco (2018), El Cañón de Sangal (2018) and La Sierra de Cazorla (2005, 2007 and 2008 respectively) with a sampling range of no more than 8 months. The Kjeldahl and Walkley and Black methods were taken into account to determine NT and CO respectively, from organic matter. Significant increases in NT and CO were observed, as well as a non-significant decrease in the carbon/nitrogen ratio in all the burned soils compared to the controls. After forest fires, the C, NT and C/N values may vary depending on the dependence between themselves and the organic matter affected, as well as according to the severity and duration of the fire. © 2021 Latin American and Caribbean Consortium of Engineering Institutions.